Preliminary data of brachyura in the mangrove of the estuarine zone of the Red river - Nhuong, Do Van; Khac, Hoang Ngoc (Academia Journal of Biology, 2015)
The preliminary investigation of Brachyura in the mangrove of the estuarine zone of the Red river have showed 62 species, belonging to 28 genera, 7 families. The majority of the encountered species are distributed commonly in the coastal area of North Vietnam. The most abundant species composition in the mangrove ecosystem belongs to two families: Grapsidae which resides mainly inside the mangrove and Ocypodidae which resides along or outside the one. The individual number and the biomass of Brachyura are higher inside the mangrove forest than outside the one.